EXPLORING RADON: FROM SOURCES AND MIGRATION FACTORS TO HEALTH EFFECTS AND MITIGATION STRATEGIES - Bello, Madaki; Muhammad, J.; Dankawu, U. M.; Musa, I. M.; David, Adamu G. K.; Umar, Halima S.; Isah, Y.; Gumel, H.; Zarma, S. S.; Ismail, Umar; Zakariyya, .; Zangina, Tasi’u (FUDMA JOURNAL OF SCIENCES, 2025)
Radon, a naturally occurring radioactive noble gas, is colorless, odorless, and can be found in indoor and outdoor air, water, and soil. It is responsible for approximately 50% of the annual effective dose of natural radioactivity. Numerous scientific studies have confirmed that radon is the second leading cause of lung cancer deaths, following tobacco use. While many review papers have been published on radon, there remains a gap in research regarding the comprehensive understanding of the potential health risks associated with radon exposure. This review focuses on recent advancements in the understanding of environmental health risks linked to radon, with particular emphasis on the key factors influencing radon migration and exposure. The review explores the characteristics of radon, conversion factors for radon exposure, and methods for its measurement. Additionally, it addresses the influencing factors for radon migration, such as geological and environmental variables, and discusses various instruments and techniques used for radon assessment. By synthesizing current knowledge and emphasizing the need for proactive measures, this review aims to fill the research gap in the understanding of radon-related health risks. It also highlights the urgent need for future research to better inform public health strategies and interventions aimed at mitigating radon exposure.
Keywords: Radon; Radioactivity; Environmental health risk; Radon in water; Health effect